Is old age always already heterosexual (and cisgender)? The LGBT Gerontology and the formation of the "LGBT elders" - Henning,Carlos Eduardo (2016)
Abstract This article seeks to present an anthropological and critical view of the development of a thriving field of knowledge production (especially present in North America) which for some decades has investigated the aging processes among lesbians, gay men and bisexual and transgender people. This field, still relatively unknown in Brazil and in South America as a whole, has been named "LGBT Gerontology ". Thus my interest lies in critically and systematically presenting and contextualizing the main trends, controversies and theoretical debates in this field, as well as their recent implications on the complex constitution, legitimation and creation of public policies concerning the new social actors, who rise concomitantly - the "LGBT seniors."